KEPEMILIKAN INSTITUSIONAL, ASSET GROWTH DAN EFISIENSI MANAGERIAL - Agus Muslim; Fitri Ismiyanti (Politeknik Negeri Lhokseumawe, 2022)
Abstract: The research objective is to examine the effect of institutional ownership, asset growth, market-to-book ratio, free cash flow on managerial efficiency. The approach used in this study is a confirmatory quantitative approach. The dependent variable is managerial efficiency. The independent variables are institutional ownership and asset growth. Market-to-book ratio control variable, free cash flow. Data obtained from the financial reports and annual reports of Construction and Property Companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period through the website www.idx.co.id. The analysis technique used to test the effect in this study is Multiple Linear Regression Analysis. As for testing managerial efficiency using the DEA test. The results showed that institutional ownership, asset growth, free cash flow had a significant positive effect on managerial efficiency. Meanwhile, the market-to-book ratio has no significant negative effect on managerial efficiency.Keywords: Institutional ownership, asset growth, market-to-book ratio, free cash flow, efficiency managerial, Construction and Property